The Virgin sculpture of San Blas de Buriñondo in Bergara: example and exception of Trinitary «Snrine of the Virgin» - González Hernando, Irene (Anales de Historia del Arte, 2006)
The studied example shows the increase of Marian worship in the Late Middle Ages, its symbolic connotations and contemporary theological concerns. Through the connection of the iconographies of Praying Virgin, Our Lady of Expectation, Sedes Sapientiae, and the «Throne of Grace» Trinity, it was praised Mary whose role was essential for divinity’s Incarnation. However, that superposition of subjects could lead to error since Christian congregation was made to believe that the complete Trinity became incarnate in Mary, despite of the fact that it was only the Son who did it. The theological concerns continued until 1745, when the pope Benedict XIV promulgated a condemning bull.
Keywords: Medieval iconography; Virgin Mary; Shrine of the Virgin; Trinity; Gothic sculpture; Council of Trent (1545-1563)